INDICATORS FOR EVALUATION OF SUSTAINABLE MOBILITY - Machado, Laura; Merino, Emilio; Mikusova, Miroslava (Doprava a spoje, 2011)
This article aims to select a set of adequate indicators for monitoring the sustainability of urban mobility, a tool that assist the planning of mobility and show the priorities investment of public resources.The indicators were selected from the following criteria: existence of data, reliability of sources and which had a sampling frequency annual. These restrictions show that there is a lack of information at the municipalities, especially in cities of medium and small size, in relation to environmental issues, non-motorized transport and urban public transport by bus.